Early Pathologic Findings of Bronchiolitis Obliterans after Allogeneic Hematopoietic Stem Cell Transplantation: A Proposal from a Case. (22nd August 2012) - Nakamoto-Matsubara, Rie; Nishikii, Hidekazu; Yamada, Kenji; Ito, Masafumi; Hasegawa, Yuichi; Kurita, Naoki; Obara, Naoshi; Okoshi, Yasushi; Suzukawa, Kazumi; Yokoyama, Yasuhisa; Sakata-Yanagimoto, Mamiko; Noguchi, Masayuki; et al.
Abstract : Bronchiolitis obliterans (BO) is one of the serious, noninfectious pulmonary complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Early diagnosis of BO is usually difficult because patients are often asymptomatic at an initial stage of the disease and pathologic findings are available mostly at the late stages. Therefore, the diagnosis of the disease is based on the pulmonary function test using the National Institute of Health consensus criteria. Here, we report a case of slowly progressive BO. A biopsy specimen at an early stage demonstrated alveolar destruction with lymphocyte infiltration in bronchial walls and mild narrowing of bronchioles without fibrosis, those were strongly indicative of initial pathologic changes of BO. Definitive BO followed, which was proven by both clinical course and autopsy. While alloreactive lymphocytes associated with chronic graft-versus-host disease are believed to initiate BO, we present a rare case that directly implies such a scenario.